2012
DOI: 10.1063/1.3678598
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of polarization and space charges in semiconducting ferroelectrics

Abstract: High-temperature ferroelectric behaviors of poly(vinylidene fluoride-trifluoroethylene) copolymer ultrathin films with electroactive interlayers J. Appl. Phys. 111, 064506 (2012) The influence of Mn substitution on the local structure of Na0.5Bi0.5TiO3 crystals: Increased ferroelectric ordering and coexisting octahedral tilts J. Appl. Phys. 111, 064109 (2012) The improved polarization retention through high-field charge injection in highly strained BiFeO3 thin films with preferred domain orientations App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…From a theoretical point of view, the ferroelectric polarization affects the transport behavior in semiconductors by means of changes in the band bending and electrical field effects (Batra et al, 1973,Blom et al, 1994,Qin et al, 2009,Suryanarayana and Bhattacharya, 2012. It has been observed in experimental and numerical works (Ge et al, 2011,Wang et al, 2011,Yi et al, 2011) that polarization-modulated Schottky-like barriers at metal/ferroelectric interfaces produce a switchable rectifying behavior in a ferroelectric thin film.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…From a theoretical point of view, the ferroelectric polarization affects the transport behavior in semiconductors by means of changes in the band bending and electrical field effects (Batra et al, 1973,Blom et al, 1994,Qin et al, 2009,Suryanarayana and Bhattacharya, 2012. It has been observed in experimental and numerical works (Ge et al, 2011,Wang et al, 2011,Yi et al, 2011) that polarization-modulated Schottky-like barriers at metal/ferroelectric interfaces produce a switchable rectifying behavior in a ferroelectric thin film.…”
Section: Introductionmentioning
confidence: 97%
“…There are different approaches to model the polarization-field (P-F) relation. The models based on Landau and Devonshire theories (Smith, 2001,Chandra, 2006, make use of the relation between the free energy W with the polarization W(P) and relate the electric field and the polarization as F = dW(P)/dP (Smith, 2001,Suryanarayana andBhattacharya, 2012). An approximation of this model is based on the hyperbolic tangent (tanh) function (Smith, 2001).…”
Section: Spatially Dependent Polarizationmentioning
confidence: 99%
“…In spite of a plethora of studies discussing how the ferroelectric state can be tailored, the naturally forming depletion charges due to ionization of impurities creating shallow levels or vacancies accepting/donating carriers in the system have put serious limitations on reliability and functionality. Shallow level impurity effects in ferroelectrics have been computationally studied mostly with emphasis on their impact on the domain structures, domain pinning [31,[40][41][42] and hystereses [32,39,[43][44][45]. Among these works, Xiao et al [40] previously showed that 180 • electrical domain walls are free of oxygen vacancies acting as donors while, in contrast to what has been thought, elastic 90 • domain walls can be decorated with these defects and the same conclusion was reached in [33].…”
Section: Introductionmentioning
confidence: 97%
“…时效初期, 噪声项及系统体积自由能的 降低提供的相变驱动力大于铁电畴的形核能垒, 系 统内产生起伏形成核胚并成为核心; 噪声项去除后, 体积自由能的降低处于主导地位, 铁电畴长大及至 充满整个模拟区域, 90°及 180°反向畴形成, 前者有 利于降低应变能, 后者有利于降低偶极距交互能, 铁 电畴数目较多但形貌不规则, 畴壁形成但形态不规 则, 如图 1(a)所示. 随着时效时间的增加, 铁电畴继 续长大, 其通过吞噬的方式长大, 包括同畴之间的吞 噬(由于合并)及异畴之间的吞噬(由于极化反转), 如 图 1(c), (d)及(e)圆内所示; 铁电畴数目先急剧减少 铁电畴的尺寸、数目、形貌及分布不再变化, 其形貌 为平行四边形状, 180°反向畴沿45°方向规则分布, 90°反向畴呈阶梯状规则分布(与张良莹和姚熹 [15] , Wang 等人 [16] , Iwata 等人 [17] , Burnett 等人 [18] 及 Yao 等 人 [19 [20] , Zheng 等人 [21] , Suryanarayana 和 Bhattacharya [22] , So 等人 [23] , Ong 和 Musleh [24] , Lohse 等人 [25] 及 Picinin 等人 [26] 得到的结论 相符; 平均应变的最大值无明显变化, 最小值明显减小. 图 9 为温度不同时矫顽电场和剩余极化随交变 电场频率的变化.…”
Section: 参数选取unclassified
“…图 9 为温度不同时矫顽电场和剩余极化随交变 电场频率的变化. 可以看出, 温度和交变电场频率对 矫顽电场和剩余极化有显著的影响, 相同温度下, 随 着交变电场频率的增加, 矫顽电场和剩余极化均先 快速增加接着增速变缓最后增速趋于恒定, 其中矫 顽电场的增幅较大, 但不同温度下的增幅变化不大, 剩余极化的增幅不一, 温度较低时增幅较小, 温度较 高时增幅较大; 相同交变电场频率下, 温度越高, 矫 顽电场及剩余极化越小(与 Stolichnov 等人 [13] , Yang 等人 [20] , Suryanarayana 和 Bhattacharya [22] , Ong 和 Musleh [24] , Wu 等人 [27] , Yuan 等人 [28] 及 Tura 等人 [29] 得到的结论相符), 且随着交变电场频率的增加, 矫 顽电场的减幅变大, 剩余极化的减幅变小.…”
Section: 参数选取unclassified